2017
DOI: 10.14198/jhse.2017.124.02
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stretching is effective as static stretching at increasing flexibility

Abstract: This study examined the effect of dynamic and static (standard) stretching on hamstring flexibility. Twentyfive female volleyball players were randomly assigned to dynamic (n = 12) and standard (n = 13) stretching groups. The experimental group trained with repetitive dynamic stretching exercises, while the standard modality group trained with static stretching exercises. The stretching interventions were equivalent in the time at stretch and were performed three days a week for four weeks. Both stretching gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In previous study Cem et al and Fırtın et al conducted research comparing the acute effects of static and dynamic stretching exercises on flexibility, agility, and anaerobic performance in professional football players, which showed that aerobic running combined with static or dynamic stretching increased the flexibility more effectively than aerobic running alone. 15,16 The result from the statistical analysis of this study supported the alternative hypothesis which stated that there is a beneficial effect to the subjects treated with PNF stretching and dynamic stretching on flexibility, balance, and agility. Hence, above results showed that subjects treated with PNF and Dynamic Stretching exercises showed significant improvement in flexibility, balance, and agility in collegiate level badminton players having hamstring tightness.…”
Section: Discussionsupporting
confidence: 74%
“…In previous study Cem et al and Fırtın et al conducted research comparing the acute effects of static and dynamic stretching exercises on flexibility, agility, and anaerobic performance in professional football players, which showed that aerobic running combined with static or dynamic stretching increased the flexibility more effectively than aerobic running alone. 15,16 The result from the statistical analysis of this study supported the alternative hypothesis which stated that there is a beneficial effect to the subjects treated with PNF stretching and dynamic stretching on flexibility, balance, and agility. Hence, above results showed that subjects treated with PNF and Dynamic Stretching exercises showed significant improvement in flexibility, balance, and agility in collegiate level badminton players having hamstring tightness.…”
Section: Discussionsupporting
confidence: 74%
“…Ideally, model training would be done simultaneously with another preparatory stage of therapy. Prior to active therapy treatment, clinicians often have patients do a warm-up exercise of a duration highly dependent on the patient, but 10 min is common (Coons et al, 2017 ). Thus, the model training sequence presented herein can be completed during this “warm up” time, and would not disrupt therapy time that would otherwise be used for active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…After that the total score is calculated, according to which the level of somatic health of pupils is determined. The total quantitative assessment in scores allows attributing pupil to a particular functional level: low (0-3 points); below average (4-6); average (7)(8)(9)(10)(11); above average (12)(13)(14)(15); and high (16)(17)(18). Measurement in control tests at the beginning and at the end of the pedagogical experiment was conducted under the same pedagogical conditions.…”
Section: Methodsmentioning
confidence: 99%